Low‐Coordinated CoNC on Oxygenated Graphene for Efficient Electrocatalytic H2O2 Production. (21st October 2021) - Gong, Haisheng; Wei, Zengxi; Gong, Zhichao; Liu, Jingjing; Ye, Gonglan; Yan, Minmin; Dong, Juncai; Allen, Christopher; Liu, Jianbin; Huang, Kang; Liu, Rui; He, Guanchao; et al.
Abstract: Electrochemical H2 O2 production through the 2‐electron oxygen reduction reaction (ORR) is a promising alternative to the energy‐intensive anthraquinone process. Herein, by simultaneously regulating the coordination number of the atomically dispersed cobalt sites and the nearby oxygen functional groups via a one‐step microwave thermal shock, a highly selective and active CoNC electrocatalyst for H2 O2 electrosynthesis that exhibits a high H2 O2 selectivity (91.3%), outstanding mass activity (44.4 A g −1 at 0.65 V), and large kinetic current density (11.3 mA cm −2 at 0.65 V) in 0.1 m KOH is obtained. In strong contrast to the typical CoN4 moieties for the 4‐electron ORR, the present CoNC catalyst possesses a low‐coordinated CoN2 configuration and abundant epoxide groups, which work in synergy for promoting the 2‐electron ORR, as demonstrated by a series of control experiments and theoretical simulations. This study may provide an effective avenue to modulating the composition and structure of electrocatalysts at the atomic scale, leading to the development of new electrocatalysts with unprecedented reactivity. Abstract : A low‐coordinated CoN2 C single‐atom catalyst containing abundant COC epoxide groups is developed via a transient microwave thermal shock with the merits of optimized electronic structure and exceptional performance for H2 O2 production.